Cartas de Manuel Rodríguez Cabrero a Roberto H. Todd (1928-1944) - Todd, Roberto H.; Rodríguez Cabrero, Manuel (My University, 1944)
Acta de nacimiento de Geraldo Forrest (incluye copia del acta).
Keywords: Rodríguez Cabrero, Manuel--Correspondence.; Rodríguez Cabrero, Manuel--Correspondencia.; Todd, Roberto H.--Correspondence.; Todd, Roberto H.--Correspondencia.